Bidirectional Crosstalk Between Hypoxia Inducible Factors and Glucocorticoid Signalling in Health and Disease - Vanderhaeghen, Tineke; Beyaert, Rudi; Libert, Claude (Frontiers in Immunology, 2021)
Glucocorticoid-induced (GC) and hypoxia-induced transcriptional responses play an important role in tissue homeostasis and in the regulation of cellular responses to stress and inflammation. Evidence exists that there is an important crosstalk between both GC and hypoxia effects. Hypoxia is a pathophysiological condition to which cells respond quickly in order to prevent metabolic shutdown and death. The hypoxia inducible factors (HIFs) are the master regulators of oxygen homeostasis and are responsible for the ability of cells to cope with low oxygen levels. Maladaptive responses of HIFs contribute to a variety of pathological conditions including acute mountain sickness (AMS), inflammation and neonatal hypoxia-induced brain injury. Synthetic GCs which are analogous to the naturally occurring steroid hormones (cortisol in humans, corticosterone in rodents), have been used for decades as anti-inflammatory drugs for treating pathological conditions which are linked to hypoxia (i.e. asthma, ischemic injury). In this review, we investigate the crosstalk between the glucocorticoid receptor (GR), and HIFs. We discuss possible mechanisms by which GR and HIF influence one another, in vitro and in vivo, and the therapeutic effects of GCs on HIF-mediated diseases.